L-R: Pearl Drake, Alex Allen, Albert Drake and Alf Jarvis (1930)
Front row: Pearl Drakeand Alex Allen. Back row: Albert Pike and Alf Jarvis. This collection contains copies made in 1998 of original photographs gathered by the Haystack Reunion Committee for publication in their booklet Haystack Reflections (1997).